Ansiedad y depresión posparto a largo plazo de las madres con COVID-19 durante el embarazo - Tayfun Vural (2022)
The COVID-19 pandemic is associated with negative mental outcomes in the earlypostpartum period. Objective: To assess the long-term postpartum mental health ofwomen infected with COVID-19 during pregnancy. Methods: Cross-sectional studyin 101 pregnant women who gave birth in a tertiary center during the COVID-19pandemic, between March 31, 2020, and November 30, 2021. The pregnant womenwere classified into 2 groups as COVID-19 positive (study group, n=52) and COVID-19negative (control group, n=49). Sociodemographic and obstetric data were collectedby questionnaire in the early (≤6 months) and late (6-18 months) postpartumperiods. Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) scoreswere calculated by analysis of the participants' data. Results: The mean BDI scoreand the rate of depression (BDI score >13) in COVID-19 positive patients were higherin the early postpartum period than in the late postpartum period. According tomultivariate linear regression analysis, there was a significant correlation betweenthe BDI score of COVID-19 patients and educational level and employment status.According to the same analysis, there was a significant correlation between the BAI score of COVID-19 patients and spousal support, marital relationship, and birth-related diseases. We found that COVID-19 positive and COVID-19 negative patients had similar BDI and BAI scores in the early (≤6 months) and late (6-18 months)postpartum periods. In addition, rates of anxiety and depression were similar inboth groups at the same postpartum periods. Conclusion: In our study, COVID-19infection in pregnancy had no significant additional impact on long-term postpartummaternal mental health.